Peningkatan Hasil Belajar IPS Melalui Problem Based Learning di SMP Negeri 5 Wates - Fitri Mahmudhah; Esti Setiawati (Proceedings Series on Social Sciences & Humanities, 2022)
This study aims to improve social studies learning outcomes in class VIII students of SMP Negeri 5 Wates. Teachers need to take classroom action by improving the monotonous learning process, namely lecture learning using the Problem Based Learning model. The research method used is Classroom Action Research with 2 cycles, which includes planning, action, observation and reflection steps. Data collection techniques used are observation and tests. The collected data were analyzed by quantitative descriptive technique with percentage technique. The results of this study indicate that: 1) Problem Based Learning model is more interesting for students to learn and can improve students' social studies learning outcomes. 2) Learning outcomes in the initial conditions obtained an average score of 55.6 with students who completed a total of 31.25%, after using the Problem Based Learning model in the first cycle obtained an average score of 68.0 with 56.25% complete participants. Then after repairs were made in the second cycle, the average was 76.9 with 78.13% of students completed.